A comparative analysis of the addition and subtraction of fractions in textbooks from three countries - Delaney, Seán; Charalambous, Charalambos Y; Hsu, Hui-Yu; Mesa, Vilma (Taylor & Francis Online, 2010)
In this paper, we report on a comparison of the treatment of addition and subtraction of fractions in primary mathematics textbooks used in Cyprus, Ireland, and Taiwan. To this end, we use a framework specifically developed to investigate the learning opportunities afforded by the textbooks, particularly with respect to the presentation of the content and the textbook expectations as manifested in the associated tasks. We found several similarities and differences among the textbooks regarding the topics included and their sequencing, the constructs of fractions, the worked examples, the cognitive demands of the tasks, and the types of responses required of students. The findings emphasized the need to examine textbooks in order to understand differences in instruction and achievement across countries. Indeed, we postulate that within a given country there may exist a recognizable “textbook signature.” We also draw on the results and the challenges inherent in our analysis to provide suggestions and directions for future textbook analysis studies.
The final publication is available at http://www.tandfonline.com/doi/abs/10.1080/10986060903460070#.UoftohA3Hq0 This version may differ in minor ways from the published version.
Keywords: Research Subject Categories::MATHEMATICS; instruction; textbook analysis; Primary Education; Primary curriculum; Ireland; Cyprus; Taiwan; addition; subtraction; fractions; comparative study